Bahan Ajar Prakarya dan Kewirausahaan Berorientasi Potensi Lokal Kabupaten Trenggalek - Niken Karlina Saputri; Wahjoedi Wahjoedi; Agung Haryono (Graduate School of Universitas Negeri Malang, 2018)
Abstract: Based on the results of preliminary observations and interviews conducted by researchers, obtained information that the local potential in Trenggalek District still belom maximized by teachers when carrying out learning activities in the classroom. Though the learning of entrepreneurship and entrepreneurship can be used as a means of learners to develop ideas or creative ideas. So the researchers chose to develop teaching materials and entrepreneurship oriented local potential Trenggalek District with the aim that can be used as one way to increase the love of learners to their environment. Based on the research that has been implemented, obtained data that teaching materials developed effectively used to improve insight and entrepreneurship attitude of learners.Abstrak: Berdasarkan observasi awal dan wawancara dengan peneliti, diperoleh informasi bahwa potensi lokal di Kabupaten Trenggalek masih belum dimaksimalkan oleh guru ketika melaksanakan kegiatan pembelajaran di kelas. Padahal pembelajaran prakarya dan kewirausahaan dapat dijadikan sarana peserta didik untuk mengembangkan gagasan atau ide kreatifnya. Peneliti memilih untuk mengembangkan bahan ajar prakarya dan kewirausahaan berorientasi potensi lokal Kabupaten Trenggalek dengan tujuan untuk meningkatkan rasa cinta peserta didik terhadap lingkungannya. Berdasarkan penelitian yang telah dilaksanakan, diperoleh data bahwa bahan ajar ini efektif untuk meningkatkan wawasan dan sikap kewirausahaan.